Comorbidity Assessment Is Uneven Across Veterans Health Administration and Medicare for the Same Patient: Implications for Risk Adjustment. Issue 8 (August 2020) - Gidwani-Marszowski, Risha; Boothroyd, Derek; Needleman, Jack; Illarmo, Samantha; Asch, Steven M.
Abstract : Objective: Compare comorbidity identification in Medicare and Veterans Health Administration (VA) data for the purposes of risk adjustment. Data Sources: Analysis of Medicare and VA datasets for dually-enrolled Veterans receiving care in both settings, fiscal years 2010–2014. Study Design: A retrospective analysis of administrative data for a national sample of cancer decedents. Data Extraction Methods: Comorbidities were evaluated using Elixhauser and Charlson coding algorithms. Principal Findings: Clinical comorbidities were more likely to be recorded in Medicare than in VA datasets. Of 42 comorbidities, 36 (86%) were recorded at a different frequency. For example, congestive heart failure was recorded for 22.0% of patients in Medicare data and for 11.3% of patients in VA data ( P <0.001). Conclusion: There are large differences in comorbidity assessment across VA and Medicare administrative data for the same patient, posing challenges for risk adjustment.